Unipolarity and Its Influences in American Foreign Policy and the Future International Relations: Unipolarity and Its Influences in American Foreign Policy and the Future International Relations (Journal of the College of Education for Women, 2019)
AbstractThe concept of unipolar has allowed the united states of America tocontrol the rest of the internations community units through the rxclusively ofcontrol in international affairs without enabling other countries who have theability to compete with it to appear this comes as a result of it's position to allkinds of powers like military, economic and technical powers that enable it tocontinue dominating other countries, this superior control enabled it to be the(hyper power) on the international political scene so that it allowed it toexercise and implement the policy of domination against all this appearedafter its empire superiority became clear, in a unique way that have neverbeen known in human history, especially after the submission of manycountries for it, which is accompanied with the absence of system based onthe law, and the domination of the logic law of power, As the unipolar conceptflourishes the power domination and ability that the united states of Americahave and this consider with the American approach that is based on impulsionand aggression in dealing with the different political issues, as the same time,it influenced on the American foreign policy especially in the so called creativechaos, which means the presence of powers that are conflicting togetherthrough leaving the conflict to its own powers to resolve this means a kind ofdestruction chaos and lawlessness. In addition, the adoption of the politicaldiscourse in the criteria of selection and differentiation add another element tothe whole activity. Perhaps the wars crisis and disaster that happened duringthe American domination are clear evidences on the catastrophic Americanapplications in the foreign policy. The continuous adoption for this concept asthe only method between countries means the continuous tension, violenceand loss of many opportunities for growth and development this requiresevery one to reconsider the structure of the international power. Inspire of theUSA keen to uphold the status quo, if fights anyone who tries to complete withit and influences on it's interests. But this domination can't stay for a long timebecause three are many international powers who compete with the unitedstates of American in power and domination, and we can see that in thenumber of changes to make a system of multiplication even if it requires fromother countries to be aggressive.